2017
DOI: 10.1103/physrevlett.118.105001
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Fusion Born Ion Populations in Magnetically Confined Plasmas using Ion Cyclotron Emission

Abstract: Ion cyclotron emission (ICE) offers a unique promise as a diagnostic of the fusion born alpha-particle population in magnetically confined plasmas. Pioneering observations from JET and TFTR found that ICE intensity P_{ICE} scales approximately linearly with the measured neutron flux from fusion reactions, and with the inferred concentration, n_{α}/n_{i}, of fusion born alpha particles confined within the plasma. We present fully nonlinear self-consistent kinetic simulations that reproduce this scaling for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 30 publications
5
62
0
Order By: Relevance
“…First, the values of key parameters, notably the ratio of the characteristic perpend icular velocity of the energetic ions to the local Alfvén speed. This needs to be of order unity [16][17][18][19][20][21][22][23][24][25][26][27][28]. Second, the structure of the distribution of the energetic ions in velocity space, which needs to be strongly non-Maxwellian in order to excite the MCI which underlies ICE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the values of key parameters, notably the ratio of the characteristic perpend icular velocity of the energetic ions to the local Alfvén speed. This needs to be of order unity [16][17][18][19][20][21][22][23][24][25][26][27][28]. Second, the structure of the distribution of the energetic ions in velocity space, which needs to be strongly non-Maxwellian in order to excite the MCI which underlies ICE.…”
Section: Discussionmentioning
confidence: 99%
“…The value of V A differs significantly between the simulations because it is inversely proportional to the square root of the majority ion (deuteron) mass density, and hence to n e . The horizontal black line denotes f LH , below which we see excitation of the fast Alfvén wave with resonances at consecutive proton cyclotron harmonics, characteristic of the MCI [2,14,[23][24][25] which underpins ICE. Above f LH there are several weaker but significant spectrally intense regions.…”
Section: Bicoherence Analysis Of the Pic Simulation Outputmentioning
confidence: 99%
See 2 more Smart Citations
“…rapid 'tongue'-shaped deformation of flux surfaces reported in the Large Helical Device (LHD) [16]) or fast ions produced by charge exchange with NBI particles [17]. Furthermore, recent 1D3V particle-in-cell (PIC) simulation showed that the high concentrations of energetic particles can intensify the harmonic ICE [18], suggesting that the intensification in high-harmonic ICE described in Figure 3(c) and Figure 3(d) can be interpreted as the increase of fast ions at the outer edge region near the pedestal collapse. In addition, a similar 1D3V PIC simulation with time-varying local electron density reproduced the rapid stair-casing chirping of proton-ICEs observed during the pedestal collapse phase on the KSTAR [12].…”
Section: Discussionmentioning
confidence: 99%